Determinan Nilai Perusahaan Manufaktur Yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2011-2017 - Muhammad Hamdan Aninulyaqin; Endri Endri; Sigid Eko Pramono (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
The purpose of this research is to analyze the effects of managerial ownership, audit committees, investment opportunities, profitability, and corporate social responsibility (CSR) on the value of manufacturing companies. This research uses data obtained from a manufacturing account of the manufacturing company registered in the Indonesia Sharia Stocks Index (ISSI) period of 2011-2017 Analysis using the application of the panel data regression model with the e-views 9 and Microsoft excel. Studies show that the most appropriate selection of models for the data panel's regression is a fixed-effect model with the result of research that managerial ownership, profitability, and corporate social responsibility (CSR) have no significant effect on the value of manufacturing companies, while the variable committee's variables and investment opportunities have significant to the value of the company listed on the Indonesia Sharia Stocks Index (ISSI) period of 2011-2017.